Partial replacement of triticale for corn grain in starter diet and its effects on performance, structural growth and blood metabolites of Holstein calves. (27th June 2016) - Moeinoddini, H. R.; Alikhani, M.; Ahmadi, F.; Ghorbani, G. R.; Rezamand, P.
Abstract : The primary objective of this study was to examine the effects of different inclusion rates of dietary triticale replacing corn grain in starter rations of dairy calves on feed intake, average daily gain (ADG), feed efficiency, skeletal growth, fecal score, and selected blood and ruminal parameters. In all, 30 4-day-old Holstein calves (15 female and 15 male) were blocked by gender and birth weight, and then randomly allotted to three treatment groups ( n =10 calves/treatment) and received either a corn-based diet without triticale (T0), or a diet containing 16% (T16) or 32% (T32) triticale (25% and 50% corn replaced by triticale, respectively) for 10 weeks. Calves were weaned on day 43 of study and remained on the study until day 70. During post-weaning period, calves fed T32 had the lowest starter intake (1.78 kg/day; P =0.02). In contrast, ADG was not affected in pre-weaning and overall periods, but calves fed T32 had a lower ADG ( P =0.04) as compared with calves fed T0 in post-weaning period. No dietary effect was detected for feed efficiency. Dietary treatment did not affect heart girth and body length; however, height at wither and hip at weaning increased in calves fed triticale compared with T0. No detectable effects were observed in serum glucose and β -hydroxybutyrate. No difference was detected in blood urea nitrogen on day 35 either but on day 50 and day 70 the greatest concentration was recorded for calves fed T16. Compared with the control, ruminal ammonia concentration was increased for calves fed T32 (4.34 v . 7.50 mmol/l) and T16 (4.01 v . 8.12 mmol/l) on day 35 and day 50. No difference was detected in ruminal pH on day 35 or day 50; however, calves fed T32 had the lowest pH (6.11) at 70 days. No significant effect was detected in days scoured, respiratory score and general appearance. Under our experimental conditions, it appears that triticale at 16% dry matter (i.e. replacing corn grain up to 25%) in the starter diet does not have adverse effects on the performance and intake of calves. Therefore, substituting corn partially with triticale in calf starter diets may prove beneficial in places where corn is less abundant or its price is prohibitive. The low number of calves per treatment however may have limited the statistical power to detect significant differences among treatments, possibly affecting the results, which should be interpreted with caution.